A 25, 000 year record of climate and vegetation change from the southwestern Cape coast, South Africa. (January 2022) - Quick, Lynne J.; Chase, Brian M.; Carr, Andrew S.; Chevalier, Manuel; Grobler, B. Adriaan; Meadows, Michael E.
Abstract: The southwestern Cape of South Africa is a particularly dynamic region in terms of long-term climate change. We analysed fossil pollen from a 25, 000 year sediment core taken from a near-coastal wetland at Pearly Beach that revealed that distinct changes in vegetation composition occurred along the southwestern Cape coast. From these changes, considerable variability in temperature and moisture availability are inferred. Consistent with indications from elsewhere in southwestern Africa, variability in Atlantic Meridional Overturning Circulation (AMOC) was identified as a strong determinant of regional climate change. At Pearly Beach, this resulted in phases of relatively drier conditions ( 24–22.5 cal ka BP and 22–18 cal ka BP) demarcated by brief phases of increased humidity from 24.5–24 cal ka BP and 22.5–22 cal ka BP. During glacial Termination I ( 19–11.7 ka), a marked increase in coastal thicket pollen from 18.5 to 15.0 cal ka BP indicates a substantial increase in moisture availability, coincident, and likely associated with, a slowing AMOC and a buildup of heat in the southern Atlantic. With clear links to glacial and deglacial Earth system dynamics and perturbations, the Pearly Beach record represents an important new contribution to a growing body of data, providing insights into the patterns and mechanisms of southwestern African climate change.